Analisis Potensi Pelanggaran Undang-Undang Persaingan Usaha Nomor 5 tahun 1999 ditinjau dari Pasal Pengecualian Keagenan dalam Industri Otomotif dan Penerapan Regulasi Block Exemption - Andrias, Mone Stepanus; Parluhutan, Dian; Saragih, Guntur Syahputra (Jurnal Hukum & Pembangunan, 2025)
The economic transformation in Indonesia and other ASEAN (Association of the South East Asian Nations) countries reflects a shift from a government-based economy to an open market system with competitive principles. The challenges faced include the rapid development of the digital economy, including Industry 4.0 which has now entered its fifth literacy. The automotive sector is one of the sectors most affected by this phenomenon. Low labour costs and high motorisation rates have attracted more car manufacturers, especially from Japan, China and Germany (Europe) to make foreign direct investments in Indonesia. Indonesia is the second largest producer and consumer of automobiles in the ASEAN region, with a market share of 25 per cent. The automotive industry employs up to 1.5 million people along the supply chain. However, despite the high potential and absorptive capacity of the automotive industry in Indonesia, the market share in this sector is dominated by only a few manufacturers with specific brands, particularly from Japan. This leads to oligopolistic market conditions that will make it difficult for new players, from other countries, to penetrate the Indonesian automotive market. Oligopolistic market conditions are caused by the pervasiveness of the practice of exclusive vertical agreements, collusive horizontal agreements and vertical integration agreements from upstream to downstream sectors or vice versa. Actually, the motive of exclusive agreement practice is to create micro-efficiency. However, this will be contradictorily confronted with macro efficiency issues, one of which is the creation of a competitive market. This issue becomes even more complex with the presence of exemption provisions, particularly in Article 50 paragraphs (a) and (e), for the enforcement of Law Number 5 Year 1999 on Business Competition related to distribution relationships, which are only attributable to agency relationships, not distribution relationships. One industry that has a very intense Principal Partnership relationship in Indonesia is the automotive industry. The nature of the partnership relationship in this business is highly dominated by the Principal so that it has the potential to conflict with the prohibitions in Business Competition Law No. 5/1999, especially in Vertical Exclusive Agreements and Vertical Integration. This study aims to analyse; First, how the potential violation of the contents of the Exclusive Vertical Agreement in the relationship between Principal and Dealer, Second, how the potential violation of the contents of Vertical Integration agreement in the relationship between Principal and Dealer; Third, how the relationship of the norm of Exclusion of Agency relationship in Article 50 with the potential violation of the prohibition of Exclusive Vertical Agreement and Vertical Integration Agreement. This research is expected to provide a reference for the Business Competition Supervisory Commission (KPPU), related Ministries, business actors and related stakeholders, in assessing potential violations of Article 15 and Article 14 of the Business Competition Law number 5/1999 in Principal and Dealer relationships in the Indonesian automotive industry. Keywords: Automotive Industry, Exclusive Vertical Agreement, Vertical Integration Agreement, Single Agent Brand Holder (ATPM), Regulation on Block Exemption